Bariatric surgery may reduce the risk of Alzheimer's diseases through GLP-1 mediated neuroprotective effects. (July 2017) - Keshava, Hari B.; Mowla, Ashkan; Heinberg, Leslie J.; Schauer, Philip R.; Brethauer, Stacy A.; Aminian, Ali
Abstract: Obesity and diabetes are associated with deficits in multiple neurocognitive domains and increased risk for dementia. Over the last two decades, there has been a significant increase in bariatric and metabolic surgery worldwide, driven by rising intertwined pandemics of obesity and diabetes, along with improvement in surgical techniques. Patients undergoing bariatric surgery achieve a significant decrease in their excess weight and a multitude of sequela associated with obesity, diabetes, and metabolic syndrome. Glucagon-like peptide 1 (GLP-1) is an intestinal peptide that has been implicated as one of the weight loss-independent mechanisms in how bariatric surgery affects type 2 diabetes. GLP-1 improves insulin secretion, inhibits apoptosis and induce pancreatic islet neogenesis, promotes satiety, and can regulate heart rate and blood pressure. Moreover, numerous studies have demonstrated potential neuroprotective and neurotrophic effects of GLP-1. Increased GLP-1 activity has been shown to increase cortical activity, promote neuronal growth, and inhibit neuronal degeneration. Specifically, in experimental studies on Alzheimer's disease, GLP-1 decreases amyloid deposition and neurofibrillary tangles. Furthermore, recent studies have also suggested that GLP-1 based therapies, new class of antidiabetic drugs, have favorable effects on neurodegenerative disorders such as Alzheimer's disease. We present a hypothesis that bariatric surgery can help delay or even prevent the onset of Alzheimer's disease in long-term by increasing the levels of GLP-1. This hypothesis has a potential for many studies from basic science projects to large population studies to fully understand the neurological and cognitive consequences of bariatric surgery and associated rise in GLP-1.